2020
DOI: 10.13106/jafeb.2020.vol7.no9.159
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure:The Case in Vietnam

Abstract: This is a quantitative research, underpinned by the philosophy of natural science and deduction approach that examines the impact of the various aspects of corporate governance mechanism on the choice of capital structure of Vietnamese listed firms. We focus on the effect of factors such as the board size, the board independence, and especially different ownership structures, which include the managerial ownership, the state ownership, the concentrated ownership, and the foreign ownership. They are the main sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…The study finds that companies have improved their market equity by opting for a capital structure solution. Vu et al (2020), Investigated 12 firms in the chemical industry in Stock Exchange for the term 2009-2013. In the mathematical analysis, they used correlation analysis and regression to study the relationship between the company's capital structure and financial results and found asset sales to be variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study finds that companies have improved their market equity by opting for a capital structure solution. Vu et al (2020), Investigated 12 firms in the chemical industry in Stock Exchange for the term 2009-2013. In the mathematical analysis, they used correlation analysis and regression to study the relationship between the company's capital structure and financial results and found asset sales to be variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmad et al (2017) proves that profitability, asset structure, firm size and liquidity have a simultaneous effect capital structure. Vu et al, 2020 examined the influence of the board size, the board independence, and especially different ownership structures, which include the managerial ownership, the state ownership, the concentrated ownership, and the foreign ownership of the capital structure in Vietnam. Vu et al research proved that only the board size, state ownership and concentrated ownership have a positive impact, while foreign ownership has a negative effect on capital structure.…”
Section: A Capital Structurementioning
confidence: 99%
“…Determination in decisions related to capital structure is one of the important decisions in business (Vu et al, 2020). Determining the company's capital structure will influence the company's funding sources in the future, cost of capital, risk character, liquidity position, investor return and firm valuation (Bajaj et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Musfiqur & Farjana, 2018). Therefore, board independence plays a crucial role in reducing agency conflict and is one of the most important elements of corporate governance mechanism (Vu, Tran, Doan, & Le, 2020). Studying the data of 127 large Indian firms in the period of 10 years from 2004 to 2013, Goel, Bansal, and Sharma (2015) revealed that an increase in the independence of board leads to adoption of a conservative approach to short-term capital management, which negatively affected working capital efficiency.…”
Section: Board Independencementioning
confidence: 99%